Insulin resistance and its correlation with chemerin and visfatin in Saudi patients with hyperthyroidism - Al Doghaither, Huda A.; Alshaikh, Eman M.; Omar, Ulfat M.; Alsufiani, Hadeil M.; Mansouri, Rasha A.; Tarbiah, Nesrin I.; Alshaikh, Abdelrhman A.; Alshaikh, Afnan M. (International Journal of Health Sciences, 2019)
Objective: This study aimed to assess the relationship between chemerin and visfatin concentrations and insulin resistance in Saudi women with hyperthyroidism. Materials and Methods: Seventy healthy participants and 70 participants with hyperthyroidism were recruited for the study. Concentrations of chemerin, visfatin, thyroid profile, fasting glucose, insulin, and homeostatic model assessment of insulin resistance (HOMA-IR) were measured. Results: Hyperthyroid patients showed significantly higher concentrations of fasting glucose and insulin (P < 0.001) and significant increases in HOMA-IR values than the control group. Spearman’s correlation coefficient analysis showed that thyroidstimulating hormone was negatively correlated with glucose, insulin, and HOMA-IR, while free triiodothyronine was positively correlated with the same parameters. Total triiodothyronine and total thyroxine also showed a significant positive correlation with glucose, and the levels of thyroglobulin were also positively correlated with insulin and HOMA-IR. Furthermore, chemerin levels correlated positively with glucose, insulin, and HOMA-IR. Inversely, visfatin was negatively correlated with insulin and HOMA-IR. Conclusion: A significant relationship was observed between adipokines and thyroid profile, glucose, insulin, and insulin resistance in hyperthyroid patients. This suggests that visfatin and chemerin levels might affect insulin sensitivity in conjunction with thyroid hormones and thus may alter the metabolism of glucose and leads to insulin resistance.